"NMR+" shale oil experimental technology system and application - Yujiang SHI; Zhehao ZHANG; Jianbin ZHAO; Yanying LUO; Jinbin WAN; Guofen HE; Chenjun ZHANG; Zuzhi HU (Shiyou shiyan dizhi, 2025)
To accurately obtain the key reservoir evaluation parameters such as porosity, oil saturation, and movable oil saturation in shale oil, an experimental technology system "NMR+" was established based on core nuclear magnetic resonance (NMR), combined with helium gas method, heavy water inhibition method, and multi-temperature heating method. Through this set of experimental workflow, multiple petrophysical parameters were obtained. Total porosity was obtained via the "NMR + helium" method by measuring the content of retained and escaping fluids in the cores. The "NMR + heavy water inhibition" method determined the distribution and content of different fluids using 2D NMR spectra based on the principles of heavy water inhibition and capillary imbibition, thereby obtaining oil saturation. The "NMR + multi-temperature heating" method determined the initial temperature point at which heavy hydrocarbons began to move and the amount of escaped hydrocarbon, based on the differences in 2D NMR distributions before and after heating, thereby obtaining movable oil saturation. This technical system was applied to fresh organic-rich shale samples from the third submember of the seventh member of the Triassic Yanchang Formation (Chang 73) (2 285.26 m) of well X in the Longdong area, Ordos Basin. A total porosity of 5.5%, oil saturation of 53.66%, and movable oil saturation of 42.68% were determined. At the same time, based on the experimental results, a 4 ms T2 cut-off value for movable porosity was calculated for this reservoir submember using NMR logging. The establishment and application of the "NMR+" experimental technology system for shale oil have enriched the laboratory methods and approaches for obtaining core porosity and saturation.